2020
DOI: 10.3390/ijerph17218245
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Mental Health among Anesthetists during the COVID-19 Pandemic

Abstract: Anesthetist-intensivists who treat patients with coronavirus disease 19 (COVID-19) are exposed to significant biological and psychosocial risks. Our study investigated the occupational and health conditions of anesthesiologists in a COVID-19 hub hospital in Latium, Italy. Ninety out of a total of 155 eligible workers (59%; male 48%) participated in the cross-sectional survey. Occupational stress was assessed with the Effort Reward Imbalance (ERI) questionnaire, organizational justice with the Colquitt Scale, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 90 publications
7
135
1
7
Order By: Relevance
“…This finding is also different from a previous report that shows that both male and female students display similar stresses and negative emotions under the impact of the pandemic [ 14 ]. Meanwhile, prior studies on what happens to health care workers facing COVID-19 also indicated that females are likely to experience higher occupational stress and mental problems [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also different from a previous report that shows that both male and female students display similar stresses and negative emotions under the impact of the pandemic [ 14 ]. Meanwhile, prior studies on what happens to health care workers facing COVID-19 also indicated that females are likely to experience higher occupational stress and mental problems [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been proposed that this prolonged exposition to SARS-CoV-2 may be one of the underlying mechanisms of the post-COVID symptoms. In fact, current evidence supports the presence of psychologic and neuropsychic symptoms, e.g., anxiety, depression, or sleep disorders, in people who deal with COVID-19 patients, e.g., healthcare professionals, but also in the general population [ 32 , 33 , 34 , 35 ]. Therefore, some post-COVID-associated symptoms could also be related to the trauma caused by having contracted a potentially fatal infection.…”
Section: Is There a Timeframe For Defining Post-covid Symptoms?mentioning
confidence: 98%
“…*Total number is higher than the sum of the different categories because of missing values. 1 Small group of respondents choose testing for all cases and testing for selective cases at the same time, therefore, the total number is higher than the sample size. Characteristics N = 2310* Type of employment Full-time 2035 (88.1%) Part-time 274 (11.9%) Practice setting Academic 509 (22.0%) Non-academic 1797 (77.8%) Clinical anesthesia experience (post-training) (in years) <5 254 (11.0%) 5–9 285 (12.3%) 10–20 689 (29.8%) >20 1082 (46.8%) Formal protocol for managing COVID-19 cases Well-defined 1803 (78.1%) Partially-defined and other 506 (21.9%) Formal training for managing COVID-19 cases Yes 1158 (50.1%) No 1152 (49.9%) Pre-operative COVID-19 testing 1 All surgical and procedural cases 1660 (72.0%) Selective cases and other 812 (35.1%) …”
Section: Resultsmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID-19) was declared a global pandemic in March 2020. Transmission to healthcare workers was reported early in the pandemic and remains a significant contributor to stress and anxiety among anesthesiologists 1 . Aerosol generating procedures such as tracheal intubation increase the risk of SARS-CoV-2 infection for healthcare providers [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%